The Influence of Green Governance, Implementation of Energy Accounting, and Green Human Resource Management on Sustainability Performance: An Empirical Study in the Hospitality Industry in Bali - Komang Adi Kurniawan Saputra; Putu Ayu Sita Laksmi (Universitas Pendidikan Ganesha, 2024)
This research aims to conduct an empirical study on the relationship between stakeholder pressure in the form of green governance, the implementation of energy accounting, and green human resource management, and their impact on sustainability performance. The study focuses on the hospitality industry, specifically star-rated hotels in Bali Province, Indonesia, with a population of 300 hotels. A proportionate stratified random sampling technique was employed to select the sample. Data were collected using a questionnaire instrument through survey techniques and analyzed using multiple linear regression. The originality of this study lies in the development of new variables that have not yet been explored in the current accounting research. The results indicate that green governance, energy accounting, and green human resource management have a significant positive influence on sustainability performance. The findings contribute to the development of stakeholder theory and provide practical insights for hotel management on developing green strategies and achieving the green hotel designation, which aligns with societal and customer legitimacy goals. Additionally, the study offers policy implications for enhancing the supervision and enforcement of existing regulations to ensure a more mandatory nature of green practices in the hospitality industry.